Membaca ulang sajak surat cinta Rendra - Kurnia, Fabiola D. (Wacana, Journal of the Humanities of Indonesia, 2002)
By deconstuctiong a text as proposed by Derrida, the text can reveals its meanings. To do this, re-reading a text is needed. For this purpose, the study attempts to understand the meanings behind Rendra;s Surat Cinta and Surat kepada Bunda by discussing the use of metaphors. Both poems are read, re-read and discussed to get their meanings. It is argued that the re-readings show opposite meanings as understiood it the first readings. Power, sex and love are among the issues explored in the two poems. Furthermore, the metaphors reflect what sort of person the "I" is.